Consensus recommendations for the use of retinoids in ichthyosis and other disorders of cornification in children and adolescents. Issue 1 (10th November 2020) - Zaenglein, Andrea L.; Levy, Moise L.; Stefanko, Nicole S.; Benjamin, Latanya T.; Bruckner, Anna L.; Choate, Keith; Craiglow, Brittany G.; DiGiovanna, John J.; Eichenfield, Lawrence F.; Elias, Peter; Fleckman, Philip; Lawley, Leslie P.; et al.
Abstract: Topical and systemic retinoids have long been used in the treatment of ichthyoses and other disorders of cornification. Due to the need for long‐term use of retinoids for these disorders, often beginning in childhood, numerous clinical concerns must be considered. Systemic retinoids have known side effects involving bone and eye. Additionally, potential psychiatric and cardiovascular effects need to be considered. Contraceptive concerns, as well as the additive cardiovascular and bone effects of systemic retinoid use with hormonal contraception must also be deliberated for patients of childbearing potential. The Pediatric Dermatology Research Alliance (PeDRA) Use of Retinoids in Ichthyosis Work Group was formed to address these issues and to establish best practices regarding the use of retinoids in ichthyoses based on available evidence and expert opinion.